Pore structure characteristics of admixture shotcrete and its quantitative relationship with mechanical properties in high geothermal environment - Wei Wang; Shaohui Zhang; Yan Wang; Jian Yuan; Ditao Niu (Journal of Materials Research and Technology, 2024)
The high geothermal environment during tunnel construction leads to the abnormal porosity and decreased mechanical properties of shotcrete, but its degradation mechanism is still unclear. The compressive strength, flexural strength, and stress-strain curve of shotcrete with 10 %–30 % fly ash (FA) and slag (SA) with curing temperature of 80 °C and curing humidity of 55 ± 2 % were studied. The types and microstructure of hydration products were researched through XRD and SEM. Different from the traditional method of calculating the fractal dimension of the whole pore size measured by MIP, the partition fractal dimension based on pore diameter classification is innovatively adopt to reflect the pore structure surface area, pore content, and tortuosity. Moreover, the quantitative relationship between the fractal dimension of pore structure and mechanical properties was analyzed by rough set theory. The strength of shotcrete with FA decreases by 12.9 %–13.1 % under 80 °C curing. As a contrast with 10 %–30 % SA to enhance its 3.2 %–13.1 %. Both FA and SA can increase the flexural strength of shotcrete by 1.2 %–33.3 %. The strain of shotcrete with FA or SA is the largest when the content is 20 %, but the ultimate strain decreases with the extension of curing age. The main pore structure type of shotcrete with FA and SA is transition pore (10 nm ∼ 100 nm), accounting for 48.86 % ∼ 57.28 % and 54.52 % ∼ 62.03 % of the total pore volume, and the addition of 20 % FA significantly reduces the large pore (≥1000 nm) of shotcrete. The addition of FA and SA makes the surface of gel pores in shotcrete smoother, and makes the spatial structure of gel pores and large pore in shotcrete more complicated. The incorporation of FA and SA reduced the tortuosity of capillary pores (100 nm ∼ 1000 nm), but increased the tortuosity of gel pores (<10 nm). The pore volume of capillary and transition pores and the surface area of capillary pores have significant effects on the strength of shotcrete. However, the tortuosity of pores has little effect on the strength of shotcrete.